Relación de la inteligencia emocional y práctica docente en la Institución Educativa Pública Primaria Secundaria N° 60087 Lucille Gagne Pellerin, Río Napo Loreto 2024 - Rojas Montero, Jaime (2025)
The main objective of this research was to understand the relationship between teaching practice and emotional intelligence. This research was conducted using a quantitative, descriptive, correlational approach and a non-experimental design. The total population was 60 teachers. The sample was 100% of the institution's total population. The survey technique was used on the population, and questionnaires were used as instruments for collecting reports. The main conclusions obtained from this research were as follows: There is a significant relationship between teaching practice and emotional intelligence. Applying Spearman's Rho coefficient, where the value obtained was 0.843 and an approximate significance of 0.000 (p < 0.05), it was interpreted that as emotional intelligence increased, teaching practice also improved significantly, allowing the research hypothesis to be accepted.